Analisis Kadar Asam Sianida dalam Solanum melongena L dan Solanum quitoense L Sebelum dan Sesudah Perebusan - Sabaniah Indjar Gama; Alimuddin Alimuddin; Eva Marliana (Journal of Tropical Pharmacy and Chemistry, 2010)
ABSTRACT Analysis cyanide acid in Solanum melongena and Solanum quitoense L before and after boiling. Cyanide acid is esthabushed by argonometricm method (Volhard) with three times repetition, for each kinds of eggplants Solanum melongena L dan Solanum quitoense L. The research showed have endireated that before boiling the content of cyanide acid Solanum melongena L (Craigi eggplant 71,712 mg/kg, kopek eggplant 46,310 mg/kg, gelatik eggplant 0 mg/kg) and Solanum quitoense L (asam eggplant 30,434 mg/kg) after boiling, the cyanide acid to slop Solanum melongena (Craigi eggplant 19,321 mg/kg, kopek eggplant 6.620 mg/kg, gelatik eggplant 0 mg/kg and Solanum quitoense L (asam eggplant 3.445 mg/kg). There is significant content have been reduced of cyanide acid in Solanum melongena L dan Solanum quitoense L Keywords: Solanum melongena dan Solanum quitoense L, Cyanide acid ABSTRAK Telah dilakukan analisis asam sianida dalam Solanum melongena dan Solanum quitoense L sebelum dan sesudah perebusan menggunakan metode Volhard dengan tiga kali pengulangan. Data hasil penelitian menunjukkan kandungan asam sianida sebelum perebusan Solanum melongena (terong Craigi 71,712 mg/kg, terong kopek 46,310 mg/kg, terong gelatik 0 mg/kg) dan Solanum quitoense L (terong asam 30,434 mg/kg) sedangkan setelah dilakukan perebusan (terong Craigi 19,321 mg/kg, terong kopek 6.620 mg/kg, terong gelatik 0 mg/kg) and Solanum quitoense L (terong asam 3.445 mg/kg). Terdapat perbedaan kandungan penting yang dapat mengurangi kadar asam sianida dalam Solanum melongena L dan Solanum quitoense L. Kata kunci: Solanum melongena dan Solanum quitoense L, Asam Sianida